ORGANIZATIONAL DEMOGRAPHY: THE DIFFERENTIAL EFFECTS OF AGE AND TENURE DISTRIBUTIONS ON TECHNICAL COMMUNICATION. - Zenger, T. R.; Lawrence, B. S. (Academy of Management Journal, 1989)
Although previous researchers have proposed organizational demography as an important determinant of communication, no one has tested this relationship directly. Further, distinctions between the i...